Tron, Ares : original motion picture soundtrack [compact disc] (Null Corporation ; Walt Disney Records, 2025)
Nine Inch Nails return with over 70 minutes of new music for the motion picture Tron: Ares, featuring singles As Alive as You Need Me to Be; Who Wants to Live Forever; and more.